1987
DOI: 10.1111/j.1445-5994.1987.tb00040.x
|View full text |Cite
|
Sign up to set email alerts
|

A Dose‐ranging Study of the Antiplatelet Effect of Enteric Coated Aspirin in Man

Abstract: Enteric coated aspirin was given to eight human volunteers in escalating doses (20, 40, 60, 80, 100 mg daily), each dose being given over two weeks. In addition, to measure the maximum effect of aspirin, each volunteer was given two single doses of 600 mg of soluble aspirin. At the end of each dosing interval we measured platelet aggregation and thromboxane formation in response to four aggregating agents and to whole blood coagulation. The doses of aspirin required to inhibit platelet aggregation in response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

1988
1988
1993
1993

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
1
4
1
Order By: Relevance
“…Since thromboxane A2 is an important mediator of platelet aggregation it is not surprising that, in this study, a cumulative dose of 240 mg aspirin was able to inhibit totally platelet aggregation and ATP release induced by exogenous AA. These results are in agreement with many others (Bye et al, 1979;Herd et al, 1987;McLeod et al, 1986;Wilson et al, 1990) and also with current recommendations for the use of low-dose aspirin in the prophylaxis of cerebrovascular and cardiovascular disease (Bochner & Lloyd, 1986).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Since thromboxane A2 is an important mediator of platelet aggregation it is not surprising that, in this study, a cumulative dose of 240 mg aspirin was able to inhibit totally platelet aggregation and ATP release induced by exogenous AA. These results are in agreement with many others (Bye et al, 1979;Herd et al, 1987;McLeod et al, 1986;Wilson et al, 1990) and also with current recommendations for the use of low-dose aspirin in the prophylaxis of cerebrovascular and cardiovascular disease (Bochner & Lloyd, 1986).…”
Section: Discussionsupporting
confidence: 92%
“…Many studies have demonstrated inhibition of AAand collagen-induced platelet activation by aspirin (Bye et al, 1979;Herd et al, 1987;McLeod et al, 1986;Siebert et al, 1983) but in many of these only a limited range of aspirin doses and stimulus concentrations have been used. Aspirin has also been shown to partially inhibit ex vivo PAF-induced platelet aggregation and ATP release (Lecrubier et al, 1983;Rao et al, 1982) .…”
Section: Introductionmentioning
confidence: 99%
“…Platelet aggregation induced by sodium arachidonate was the only aggregation response to be significantly inhibited by chronic ingestion of 100 mg aspirin/day. This contrasts with the findings in man where all aggregation responses were markedly inhibited by 20 mg/day (9). In our study, ingestion of 100 mg aspirin/day did not inhibit collagen-induced aggregation although thromboxane generation induced by collagen and sodium arachidonate was reduced to 11-33% of the control values.…”
Section: Discussioncontrasting
confidence: 99%
“…Aspirin may be more effective as an antithrombotic agent if the undesirable effect on the vessel wall could be minimised or avoided, while retaining the inhibitory effect of aspirin on platelets. This may be possible using enteric-coated or slow-release aspirin in doses of 100 mg or less which have been shown to maximally inhibit platelet function (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…The production of TXA2, 5 min after the -addition of agonist, was measured by radioimmunoassay of the stable end-product, TXB2, as previously described (Herd et al, 1987). The detection limit of the assay was 0.2 ng ml' PRP or 0.6 pg/106 platelets.…”
Section: Platelet Function Testsmentioning
confidence: 99%